2017
DOI: 10.1083/jcb.201608128
|View full text |Cite
|
Sign up to set email alerts
|

VAPs and ACBD5 tether peroxisomes to the ER for peroxisome maintenance and lipid homeostasis

Abstract: Peroxisomes and the ER exchange lipids for various metabolic and anabolic reactions. In this study, Hua et al. show that the interaction between the ER-resident VAPs with the peroxisomal protein ACBD5 tethers peroxisomes to the ER. This tether is required for the exchange of lipids, including cholesterol, between the two organelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
256
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(284 citation statements)
references
References 53 publications
10
256
0
1
Order By: Relevance
“…In addition the movement of peroxisomes was increased. Simultaneously the group of Peter Kim used a parallel approach to reach the same conclusions, additionally reporting that plasmalogen synthesis is impaired when the VAPB-ACBD5 tether is disrupted 31 . Recent studies have now identified patients carrying pathogenic mutations which lead to the loss of ACBD5 protein 32-34 .…”
Section: Resultsmentioning
confidence: 85%
“…In addition the movement of peroxisomes was increased. Simultaneously the group of Peter Kim used a parallel approach to reach the same conclusions, additionally reporting that plasmalogen synthesis is impaired when the VAPB-ACBD5 tether is disrupted 31 . Recent studies have now identified patients carrying pathogenic mutations which lead to the loss of ACBD5 protein 32-34 .…”
Section: Resultsmentioning
confidence: 85%
“…A separate region, comprising amino acids 71–81, serves as the ER‐to‐peroxisome targeting signal, as judged by the fact that the deletion of this sequence caused the PEX16(Δ66‐81)‐GFP to remain in the ER. PEX16 recruits multiple PMPs to the ER as shown for two TA PMPs (PEX26 and FIS1), as well as multi‐span PMPs (PMP34, PEX11β, and PEX10), a function that is conserved in plants . This recruitment depends on amino acids 66–103 in PEX16 and is independent of PEX3 and PEX19.…”
Section: Introductionmentioning
confidence: 88%
“…In mammals, the ER has the most abundant contact sites for peroxisomes (more than 90% of peroxisomes contact the ER) followed by mitochondria (~ 20%) and LDs (~ 20%) . Recently, two independent groups identified the tethers between the ER and peroxisomes in mammals (Fig B). The ER tethers are the vesicle‐associated membrane protein (VAMP)‐associated proteins (VAPs), which are implicated in tethering several different MCSs .…”
Section: Introductionmentioning
confidence: 99%
“…The ER integral proteins VAPA and VAPB [vesicle-associated membrane protein-associated protein, referred to as VAPs here (8)] are common components of the MCS formed between the ER and various organelles (5,(9)(10)(11)(12)(13)(14). At each of these MCS, VAPs interact with different proteins that have a 7-aa sequence, known as a FFAT motif [two phenylalanines (FF) in an acidic tract (AT)] in common (15).…”
mentioning
confidence: 99%